Gamification and technology acceptance model: a systematic review and future research directions - Kalana, Mohd Hazim Afiq; Junaini, Syahrul Nizam (Journal of Education and Learning (EduLearn), 2025)
Technological advancements have popularized "gamification" in recent years, yet few studies have explored its connection to the technology acceptance model (TAM). This paper aims to enhance understanding of the relationship between gamification and TAM by systematically reviewing current research trends. Employing a systematic literature review (SLR) method, we analyzed 72 papers identified via Scopus, focusing on 13 journal papers published between 2016 and 2020 that met our criteria for in-depth analysis. Our findings indicate a significant rise in research on gamification and TAM, with nearly half of the studies (49%) incorporating new external variables into the original TAM framework. The study identifies three key themes for future research. By providing a comprehensive review, this study contributes new knowledge and offers a critical summary for further investigation into the integration of gamification with TAM, highlighting potential avenues for future research and practical application.